En los sótanos de los generales : los documentos ocultos del Operativo Cóndor / Alfredo Boccia Paz, Miguel H. López, Antonio V. Pecci, María Gloria Giménez ; [prólogo de Augusto Roa Bastos] - Boccia Paz, AlfredoRoa Bastos, Augusto (1917-2005)
Bibliografía: p. 343-354